Medición de la calidad del servicio en la atención al usuario en el proceso de matriculación de la Universidad Técnica de Cotopaxi. - Cortez Coronel, Carmen Margarita (2018)
The research was sought to determine the measurement quality in the user service that the Universidad Técnica de Cotopaxi offers. The research problem are the limitations in the user service in the enrollment process of the Universidad Técnica de Cotopaxi, since there is no a study that determines the quality of the service of enrollment. A quantitative approach was applied that allowed to measure the quality of the service in the enrolment also the descriptive and documentary research were applied as well. They were applied to develop the analyses of the results as well as to gain knowledge on the research variables. Nowadays 7962 students are registered in the academic period October 2017-In February, 2018 including to the Matriz San Felipe and its campus La Mana and Salache, Later the sample was calculated by the formula for finite information, a sample of 363 was obtained regular students to whom the instrument ES- QUAL was applied and 307 homologados students those who were evaluated by the instrument SERVQUAL, instruments that possess a level of validity of 95% and 92% respectively. The beneficiaries of the research are principally the users of the service being these about 7962 students for the current academic period, as well as the Universidad Técnica de Cotopaxi, since with the obtained results it will have clear information about the perspective of the users concerning the enrollment process, which will contribute in the improvement of the processes. Regarding to the instruments the model SERVQUAL was applied to the students of homologación who enroll without a virtual process they come to the different secretaries of faculty, an index of quality -1,16 was obtained, whereas the model ES-QUAL, was applied to the students who the regular students enroll using the online platform, a result-1,13 was obtained. When the research finished was concluded that the service of enrollment offered by the Universidad Técnica de Cotopaxi is good, since its values are near to zero, which in agreement to the theoretical frame while more nearby to zero one finds the quality index indicates that the offered service possesses total quality.